Synchronous deficits in cumulative muscle protein synthesis and ribosomal biogenesis underlie age-related anabolic resistance to exercise in humans - Brook, Matthew S.; Wilkinson, Daniel J.; Mitchell, William Kyle; Lund, Jonathan N.; Phillips, Bethan E.; Szewczyk, Nathaniel J.; Greenhaff, Paul L.; Smith, Kenneth; Atherton, Philip J. (Wiley, 2016)
Ageing is associated with impaired hypertrophic responses to resistance exercise training (RET). Here we investigated the aetiology of ‘anabolic resistance’ in older humans. Twenty healthy male individuals, 10 younger (Y; 23 ± 1 years) and 10 older (O; 69 ± 3 years), performed 6 weeks unilateral RET (6 × 8 repetitions, 75% of one repetition maximum (1-RM), 3 times per week). After baseline bilateral vastus lateralis (VL) muscle biopsies, subjects consumed 150 ml D2O (70 atom%; thereafter 50 ml week−1), further bilateral VL muscle biopsies were taken at 3 and 6 weeks to quantify muscle protein synthesis (MPS) via gas chromatography–pyrolysis–isotope ratio mass spectrometry. After RET, 1-RM increased in Y (+35 ± 4%) and O (+25 ± 3%; P < 0.01), while MVC increased in Y (+21 ± 5%; P < 0.01) but not O (+6 ± 3%; not significant (NS)). In comparison to Y, O displayed blunted RET-induced increases in muscle thickness (at 3 and 6 weeks, respectively, Y: +8 ± 1% and +11 ± 2%, P < 0.01; O: +2.6 ± 1% and +3.5 ± 2%, NS). While ‘basal’ longer term MPS was identical between Y and O (∼1.35 ± 0.1% day−1), MPS increased in response to RET only in Y (3 weeks, Y: 1.61 ± 0.1% day−1; O: 1.49 ± 0.1% day−1). Consistent with this, O exhibited inferior ribosomal biogenesis (RNA:DNA ratio and c-MYC induction: Y: +4 ± 2 fold change; O: +1.9 ± 1 fold change), translational efficiency (S6K1 phosphorylation, Y: +10 ± 4 fold change; O: +4 ± 2 fold change) and anabolic hormone milieu (testosterone, Y: 367 ± 19; O: 274 ± 19 ng dl−1 (all P < 0.05). Anabolic resistance is thus multifactorial.